Considering the amounts in each table, the difference function is given as follows:
x| 1 2 3 4
(f - g)(x)|1.74 7.41 17.21 31.34
At each value of x, the difference function (f - g)(x) is given by f(x) - g(x).
Hence, from the table given:
(f - g)(1) = f(1) - g(1) = 1,576.74 - 1,575 = 1.74.
(f - g)(2) = f(2) - g(2) = 1,657.41 - 1,650 = 7.41.
(f - g)(3) = f(3) - g(3) = 1,742.21 - 1,725 = 17.21.
(f - g)(4) = f(4) - g(4) = 1,831.34 - 1,800 = 31.34.
More can be learned about functions at https://brainly.com/question/25537936